The intellectual development of Iván Rodríguez Chávez: between the humanities and law - Ward, Thomas (2023)
This text reviews the intellectual development of Iván Rodríguez Chávez and how this ended up shaping his thinking on the relationship between the humanities, law and the university as a fundamental basis for promoting Peruvianism. To this end, it begins with an account of his teachers, such as José Russo Delgado, Estuardo Núñez Hague, Luis Alberto Sánchez, among others, who inculcated in him the knowledge and academic practices that he would implement in his pedagogical exercise as an educator and later as rector of the Ricardo Palma University. It also exposes four of his intellectual predilections that are reflected in different books and interviews: humanities and law, society, the university and the relationship between the university and society, problems and solutions.